2016
DOI: 10.1016/j.physletb.2016.08.066
|View full text |Cite
|
Sign up to set email alerts
|

R-parity violating supersymmetry at IceCube

Abstract: The presence of R-parity violating (RPV) supersymmetric interactions involving high-energy neutrinos can lead to resonant production of TeV-scale squarks inside large-volume neutrino detectors. Using the ultra-high energy neutrino events observed recently at the IceCube, with the fact that for a given power-law flux of astrophysical neutrinos, there is no statistically significant deviation in the current data from the Standard Model expectations, we derive robust upper limits on the RPV couplings as a functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 149 publications
0
27
0
Order By: Relevance
“…We end this section by noting that we have not used angular information, nor have we allowed the flavor composition of the astrophysical flux to vary. Reference [54] has shown that this can help, notably by removing theν e component leading to the Glashow peak. We anticipate that angular information would lead to a slight improvement in the significance of our results, whereas allowing the flavor composition to vary would weaken it, and require extra motivation to explain the lack of aν e flux.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We end this section by noting that we have not used angular information, nor have we allowed the flavor composition of the astrophysical flux to vary. Reference [54] has shown that this can help, notably by removing theν e component leading to the Glashow peak. We anticipate that angular information would lead to a slight improvement in the significance of our results, whereas allowing the flavor composition to vary would weaken it, and require extra motivation to explain the lack of aν e flux.…”
Section: Resultsmentioning
confidence: 99%
“…This distinction is important, as the different contributions to the event rates have very different topological signatures. These are crucial: previous studies [50,52,53,56,57] have examined the impact of an extra leptoquark-induced interaction (or a similar R-parity violating SUSY model [54]) on the best-fit fluxes reported by the IceCube Collaboration. However, this is not self-consistent, as the fluxes were derived using the same data set.…”
Section: B Comparison With Icecube Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Additional BSM physics can be constrained by IceCube, whether it alters the neutrino flavor composition or not. High-energy neutrinos can resonantly produce TeV-scale squarks, and upper limits on the R-parity-violating couplings can be derived as a function of the squark's mass [103].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting alternative is the existence of secret neutrino interactions with a light (MeV-scale) Z [23][24][25][26] or light neutrinophilic neutral scalar [27][28][29], in which case the resonance could again fall in the multi-TeV to PeV range which will be accessible at IceCube. Heavy (TeV-scale) resonances induced by neutrino-nucleon interactions mediated by exotic charged particles, such as leptoquarks [30][31][32][33], or squarks in R-parity violating supersymmetry [34][35][36][37]. have also been discussed.…”
mentioning
confidence: 99%